Transvenous Renal Biopsy of Critically Ill Patients: Safety and Diagnostic Yield. Issue 3 (March 2019) - de Chambrun, Marc Pineton; Cluzel, Philippe; Brocheriou, Isabelle; Bréchot, Nicolas; Hékimian, Guillaume; Turki, Mohamed-Wafik; Franchineau, Guillaume; Rouvier, Philippe; Bourcier, Simon; Bureau, Côme; Nieszkowska, Ania; Le Guennec, Loïc; et al.
Abstract : Objectives: Transvenous renal biopsy is an alternative way to obtain kidney samples from patients with bleeding risk factors (e.g., antiplatelet therapy and anticoagulation or coagulation disorders). This study was undertaken to determine the safety and diagnostic yield of transvenous renal biopsy of critically ill patients. Design: Monocenter, retrospective, observational cohort study. Setting: A 26-bed French tertiary ICU. Patients: All patients undergoing in-ICU transvenous renal biopsy between January 2002 and February 2018. Interventions: None. Measurements and Main Results: Eighty patients (male/female sex ratio, 0.95; mean ± SD age, 47.3 ± 18.3 yr) were included. A histologic diagnosis was obtained for 77 patients (96.3%), with acute tubular necrosis being the most frequent: 23 (29.9%). A potentially treatable cause was found for 47 patients (58.7%). The numbers of patients with 0, 1, 2, or 3 factors (i.e., antiplatelet therapy, thrombopenia [< 150 G/L], and preventive or curative anticoagulation) at the time of the biopsy were, respectively: seven (8.8%), 37 (46.2%), 31 (38.7%), and five (6.3%). Four (5%) and two (2.5%) patients, respectively, had renal hematoma and macroscopic hematuria; none required any specific treatment. Six patients (7.5%) died in-ICU, and 90-day mortality was 8 of 80 (10%). No death was related to transvenous renal biopsy, and median biopsy-to-death interval was 38 days (interquartile range, 19.7–86 d). Conclusions: Based on this cohort of ICU patients with acute kidney injury, transvenous renal biopsy was safe and obtained a high diagnostic yield for these selected critically ill patients, even in the presence of multiple bleeding risk factors. Abstract : Supplemental Digital Content is available in the text.